P3.393 Iknowmine.org - a Comprehensive Wellness Website For Alaska Native Youth. (13th July 2013) - Jessen, C; Revels, T; Ferguson, J
Abstract : Background: Alaska has some of the highest rates of Chlamydia and gonorrhoea in the United States. The Centers for Disease Control and Prevention (CDC) ranked Alaska #1 for Chlamydia and #3 for gonorrhoea in 2010. When iknowmine.org first launched in December 2009, Alaska was experiencing a gonorrhoea outbreak and endemic rates of Chlamydia. Alaska Native people, especially youth and women, shouldered the largest burden. Evidence from a focus group project with Alaska Native youth suggested that sexual health initiatives need to use the internet to reach adolescents with STD/HIV education and testing messages. Methods: To help Alaska Native youth on their wellness journey, iknowmine was recreated as a culturally appropriate, readily accessible and comprehensive youth health resource addressing many issues that matter to youth – relationships, emotional health, nutrition, safety, drug and alcohol use and sexual health. On iknowmine.org youth can find accurate health information on a variety of topics, text to ask health questions and order free condoms and at-home STD testing kits, download educational materials, watch digital storeys and more. The website also incorporates social media like Facebook and Twitter to reach a larger audience. Results: Between January 2010 and January 2013, 23, 887 new visitors frequented iknowmine.org. Since its inception, 514 visitors have registered as iknowmine users. Iknowmine.org has received 226 condom orders, which equals about 4, 520 condoms that were mailed to rural and urban Alaska residents. Free at-home STD testing is offered through a partnership with the Johns Hopkins University's I Want the Kit (IWTK) programme. In 2012, 342 testing kits were ordered and 132 returned with an overall return rate of 39%. Among returned kits, 14 participants tested positive for Chlamydia, two for gonorrhoea and Chlamydia and four for trichomonas. Conclusion: Iknowmine.org has been successful in reaching a large audience with HIV/STD education and resources.